Fra helt til syndebukk: En studie av hvordan en landslagstrener i fotball kombinerer transformasjonsledelse og machiavellisk ledelse - Andersen, T. L. (Scandinavian Sport Studies Forum, 2020)
In this article the leadership style of a national football coach, in the context of the rationality of professional sport, where victory trumps everything, is being studied. The question discussed is whether the coach used his frequently communicated transformational leadership style as well as a Machiavellian leadership style, and whether the balance between these leadership styles changed when the team started to lose games. The assumption was that the Machiavellian leadership style would become more prominent when the results failed. This did not happen. The findings show that a one-sided transformational leadership style was not sufficient to maintain authority internally and externally in such a situation. An ability to balance the two leadership styles seems necessary. The study show that intellectual stimulation and involvement are two important dimensions for creating and maintaining authority related to the players, especially when results fail. Furthermore, the study shows that communication and `media-leadership` influenced the dynamics between the media and the coach. As a result, this study has highlighted the importance for coaches to also master `multi-directional leadership`.